PHARMACEUTICAL CARE AND EFFECTIVE COMMUNICATION WITH CUSTOMERS - Ardava, Elita; Gustiņa, Nelda; Šukele, Renāte; Onževs, Oskars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Nowadays, the provision of pharmaceutical care and effective communication with customers are being discussed more often. A pharmacist is a specialist in his field with specific knowledge in the field of pharmacy. Therefore, the trust from the customer’s side and a kind, informative, and professional approach from the pharmacist’s side are very important in this case. Objective: To clarify what knowledge do the pharmacy customers have about pharmaceutical care and how satisfied they are with the pharmaceutical care services. The research was conducted using a quantitative survey, the statistical analysis of the obtained data was carried out using data processing software Microsoft Office Excel 2010, 267 respondents from various regions of Latvia were surveyed. Only 37% of respondents understand meaning of pharmaceutical care. This means that most of the customers are unaware of the duties and responsibilities of a pharmacist. Most of the respondents associate pharmaceutical care with medication dispense, consultation and good customer service. It would be necessary to inform society about pharmaceutical care and its importance in healthcare. Conclusions: The hypothesis put forward in the thesis confirms that society needs to be informed about pharmaceutical care, and pharmacist duties and responsibilities.